Lead frame and surface silver plating process thereof
By using specific alloy materials and cyanide-free silver plating process, the lead frame's shortcomings in strength, hardness and corrosion resistance are solved, and higher mechanical strength, conductivity and corrosion resistance are achieved, suitable for complex working environments.
Patent Information
- Application Number
- CN202411848352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lead frames have shortcomings in strength, hardness and corrosion resistance, making it difficult to meet the stability and efficient heat dissipation needs of complex working environments.
An alloy material composed of iron, nickel, zinc, tin, silicon and copper is used as the substrate of the lead frame, and a cyanide-free silver plating process is used on its surface. The formation of pre-silver and composite silver plating layers is improved to improve conductivity and wear resistance.
It significantly improves the mechanical strength, conductivity and corrosion resistance of the lead frame, enhances its stability in complex environments and reliability of circuit transmission, while extending its service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductors, in particular to a lead frame and a silver plating process for its surface. Background Art
[0002] The lead frame is the chip carrier of the integrated circuit. It uses bonding materials (gold wire, copper wire, aluminum wire) to achieve electrical connection between the lead end of the internal circuit of the chip and the external lead. It is a key structural component in forming an electrical circuit and plays a role in connecting to external wires. Lead frames are required in most semiconductor integrated blocks and are an important basic material in the electronic information industry.
[0003] The lead frame needs to have good electrical conductivity and is generally made of single elements or alloys such as copper and iron. Compared with alloys, single metals have better electrical conductivity, but the hardness, corrosion resistance and strength of single metals cannot meet the requirements of the lead frame. Even if alloy materials are added, the effect is not satisfactory.
[0004] Therefore, we propose a lead frame and a silver plating process on its surface to improve its strength, hardness and corrosion resistance. Summary of the invention
[0005] The object of the present invention is to provide a lead frame and a surface silver plating process thereof to solve the problems raised in the prior art.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a lead frame, comprising a metal plate and a silver-plated layer; the metal plate comprises the following components: in mass percentage, iron: 2.0%-2.4%, nickel: 1.5%-2.1%, zinc: 0.5%-1.15%, tin: 0.15%-0.35%, silicon: 0.4%-0.8%, and the remainder is copper.
[0007] In the above technical scheme, iron has high mechanical strength and thermal conductivity, can withstand large external forces and vibrations, ensure that the lead frame can remain stable in a complex working environment, and good thermal conductivity helps to disperse the heat generated by electronic components during operation to prevent overheating and damage; nickel has good corrosion resistance, which helps the lead frame resist moisture or corrosion; zinc can significantly improve the mechanical strength of the lead frame, better withstand external pressure, reduce deformation, and extend service life. Zinc also has excellent electrical conductivity, which can improve the electrical conductivity efficiency of the lead frame, reduce resistance, and ensure stable circuit transmission. During the welding process, zinc can provide better wettability and adhesion, reduce welding defects, and improve the reliability of the overall circuit; tin has good electrical conductivity and corrosion resistance, reduces resistance, ensures the normal operation of electronic components, and improves the oxidation resistance and corrosion resistance of the lead frame. Silicon has good electrical conductivity and thermal conductivity, ensures that the heat generated inside the chip can be effectively dissipated, and ensures that the chip works at normal temperature. Silicon material is highly compatible in semiconductor manufacturing processes and can cooperate with other materials and processes to ensure the stability and reliability of integrated circuits.
[0008] Furthermore, the silver-plated layer includes a pre-silver-plated layer and a composite silver-plated layer.
[0009] A surface silver plating process for a lead frame comprises the following steps: Step 1: Mix iron particles, nickel particles, zinc particles, tin particles, silicon particles and copper particles, melt them to obtain alloy liquid, pour the alloy liquid into a mold, cool it, and obtain a metal plate; Step 2: placing the obtained metal plate in a pre-silvering solution to perform a pre-silvering treatment to form a pre-silvering layer to obtain a pre-silvered metal plate; Step 3: attaching a layer of dry film on the upper surface and the lower surface of the pre-silver-plated metal plate, exposing, developing, and drying, removing part of the dry film on the upper surface and the lower surface of the pre-silver-plated metal plate, and etching the exposed local area of the pre-silver-plated metal plate to obtain a pre-silver-plated lead frame; Step 4: placing the obtained pre-silver-plated lead frame in a composite silver-plating solution, performing a silver-plating treatment, forming a composite silver-plating layer, and obtaining a silver-plated lead frame.
[0010] Furthermore, in step 1, the melting temperature is 1300-1400°C, and the cooling temperature is 20-30°C.
[0011] Furthermore, iron particles: 3-28 mm, purity 99%, are sourced from Nangong Xingjiu New Materials Technology Co., Ltd.; Nickel particles: 8-12mm, purity 99.9%, from Nangong Xindun Alloy Welding Material Spraying Co., Ltd. Zinc particles: 1-6mm, purity 99.99%, from Wuhan Cypress Trading Co., Ltd. Tin particles: 2-4mm, purity 99.9%, from Tianjin Hejifeng Metal Materials Co., Ltd.; Silicon particles: 1-3mm, purity 99.99%, from Hebei Sanliujiu New Materials Technology Co., Ltd. Copper particles: 3-5mm, purity 99.9%, sourced from Hebei Teng Bimetallic Materials Co., Ltd.
[0012] Furthermore, the process conditions for exposure in step 3 are: ambient temperature 20-40° C., time 15-25 s, light intensity 500-1000 MJ; The developing time is 100-180s.
[0013] Furthermore, the process conditions for pre-silvering in step 2 are: current density 0.1-0.3A / dm 2 , temperature 20-30℃, time 3-5min.
[0014] Furthermore, the pre-silver plating solution in step 2 is prepared by the following process: Silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water are mixed and stirred uniformly, and the pH is adjusted to 9-11 to obtain a pre-silver plating solution.
[0015] Furthermore, the ratio of silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine, and deionized water is (5-9) g: (60-80) g: (10-30) g: (10-30) g: (0.8-1) L.
[0016] Further, silver nitrate: CAS No. 7761-88-8, sourced from Guangdong Xiaoda Chemical Co., Ltd.; 5,5-Dimethylhydantoin: CAS No. 503-60-6, from Hubei Huiheyuan Chemical Co., Ltd.; Nicotinic acid: CAS No. 59-67-6, from Merck reagent; 2-Hydroxypyridine: CAS No. 142-08-5, derived from McLean's reagent.
[0017] In the above technical scheme, silver nitrate is used as the main electrolyte salt, and 5,5-dimethylhydantoin and nicotinic acid are compounded to prepare a pre-silver plating solution. The pre-silver plating treatment is performed before silver plating, which can effectively prevent the replacement reaction between copper and the silver plating solution, destroy the stability of the silver plating solution, and affect the silver plating effect. Silver is a soft acid. According to the principle of soft and hard acids and bases, 5,5-dimethylhydantoin, nicotinic acid and 2-hydroxypyridine are selected as soft ligands. In an alkaline system, 5,5-dimethylhydantoin forms a complex with silver ions, which changes the reduction potential of silver ions and causes them to be reduced and deposited on the cathode. The addition of nicotinic acid and 2-hydroxypyridine can improve the dispersion performance of the pre-silver plating solution and enhance the bonding force between the pre-silver plating layer and the lead frame substrate.
[0018] Furthermore, the process conditions for silver plating in step 4 are: voltage 300-380V, current 15-25A, frequency 450-650Hz, time 0.5-1.5h.
[0019] Furthermore, the composite silver plating solution in step 4 is prepared by the following process: Half of the silver plating solution is mixed with modified titanium carbide and graphene oxide, and ultrasonically stirred, and then the remaining silver plating solution is added and stirred evenly to obtain a composite silver plating solution.
[0020] Furthermore, the mass ratio of silver plating solution, modified titanium carbide, and graphene oxide is (7-9): (0.05-0.1): (0.08-0.12).
[0021] Furthermore, the process conditions of ultrasonic stirring are: power 150-200w, time 60-80min, speed 400-600r / min.
[0022] Furthermore, graphene oxide: item number C03043, 0.5-3 μm, sourced from Beijing Juguang Yingchuang Technology Co., Ltd.
[0023] Furthermore, the silver plating solution is prepared by the following process: Silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water are mixed, stirred evenly, and the pH is adjusted to 11.5-12.5 to obtain a silver plating solution.
[0024] Furthermore, the ratio of silver nitrate, potassium sodium tartrate, ammonia water, surfactant, and distilled water is (10-20) g: (60-100) g: (60-80) mL: (3-6) mL: (0.8-1) L.
[0025] Further, ammonia: CAS No. 1336-21-6, from Merck reagent; Potassium sodium tartrate: CAS No. 6381-59-5, from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd.; The surfactant was sodium dodecyl sulfate, CAS No. 151-21-3, from Merck Reagent.
[0026] Further, the modified titanium carbide is prepared by the following process: The titanium carbide particles are placed in the above silver plating solution, and reacted by magnetic stirring. After the reaction is completed, the particles are washed and dried to obtain modified titanium carbide.
[0027] Furthermore, the mass ratio of titanium carbide particles to silver plating solution is 1:(5-7).
[0028] Furthermore, the process conditions of magnetic stirring are: temperature 20-30°C, rotation speed 200-300r / min, and time 20-30min.
[0029] Furthermore, titanium carbide: grade TiC-1, 1.5-2.0 μm, comes from Hunan Huashen Technology Co., Ltd.
[0030] In the above technical scheme, modified titanium carbide and graphene oxide are added to the silver plating solution as reinforcing phases. Titanium carbide itself has high strength and wear resistance, which can improve the overall performance of the lead frame. Silver coating of titanium carbide can make it more evenly dispersed in the silver plating solution, which helps to form a dense and uniform silver plating layer. Graphene oxide has excellent electrical conductivity, thermal conductivity and wear resistance, which can significantly improve the heat dissipation capacity of the silver plating layer, ensure the normal operation of the circuit, and enhance the wear resistance of the silver plating layer. In addition, the epoxy functional groups on the surface of the graphene oxide can form a self-assembled monolayer on the surface of the lead frame substrate, which enhances the bonding force between the silver plating layer and the lead frame substrate, prolongs the residence time of the silver plating layer on the substrate surface, thereby prolonging the service life of the lead frame. The invention uses a cyanide-free silver plating process, has higher safety and environmental protection, potassium sodium tartrate in the silver plating solution can promote radial growth of crystal grains, has a stable reaction speed, and the formed silver plating layer is relatively uniform, and potassium sodium tartrate is a natural organic acid, is environmentally friendly, and has high economic benefits; ammonia water is used as a complexing agent to react with silver ions to generate a silver complex with high stability, and a relatively dense silver plating layer can be obtained.
[0031] Compared with the prior art, the present invention has the following beneficial effects: 1. Silver nitrate was used as the main salt, and 5,5-dimethylhydantoin and nicotinic acid were compounded to prepare a pre-silver plating solution. Pre-silver plating treatment was performed before silver plating to effectively prevent the replacement reaction between copper and the silver plating solution, destroy the stability of the silver plating solution, and affect the silver plating effect. Silver is a soft acid. According to the principle of soft and hard acids and bases, 5,5-dimethylhydantoin, nicotinic acid and 2-hydroxypyridine were selected as soft ligands. In an alkaline system, 5,5-dimethylhydantoin formed a complex with silver ions, which changed the reduction potential of silver ions and caused them to be reduced and deposited on the cathode. The addition of nicotinic acid and 2-hydroxypyridine can improve the dispersion performance of the pre-silver plating solution and enhance the bonding force between the pre-silver plating layer and the lead frame substrate.
[0032] 2. Modified titanium carbide and graphene oxide are added to the silver plating solution as reinforcing phases. Titanium carbide itself has high strength and wear resistance, which can improve the overall performance of the lead frame. Silver coating of titanium carbide can make it more evenly dispersed in the silver plating solution, which helps to form a dense and uniform silver plating layer; graphene oxide has excellent electrical conductivity, thermal conductivity and wear resistance, which can significantly improve the heat dissipation capacity of the silver plating layer, ensure the normal operation of the circuit, and enhance the wear resistance of the silver plating layer. In addition, the epoxy functional groups on the surface of graphene oxide can form a self-assembled monolayer on the surface of the lead frame substrate, which enhances the bonding force between the silver plating layer and the lead frame substrate, prolongs the residence time of the silver plating layer on the substrate surface, thereby extending the service life of the lead frame.
[0033] 3. The cyanide-free silver plating process is safer and more environmentally friendly. Potassium sodium tartrate in the silver plating solution can promote the radial growth of grains, the reaction rate is stable, and the formed silver plating layer is relatively uniform. Potassium sodium tartrate is a natural organic acid, which is environmentally friendly and has high economic benefits. Ammonia water acts as a chelating agent, reacts with silver ions to generate a silver complex with higher stability, and a denser silver plating layer can be obtained. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the following specific implementations, Iron particles: 3-28mm, purity 99%, from Nangong Xingjiu New Material Technology Co., Ltd. Nickel particles: 8-12mm, purity 99.9%, from Nangong Xindun Alloy Welding Material Spraying Co., Ltd. Zinc particles: 1-6mm, purity 99.99%, from Wuhan Cypress Trading Co., Ltd. Tin particles: 2-4mm, purity 99.9%, from Tianjin Hejifeng Metal Materials Co., Ltd.; Silicon particles: 1-3mm, purity 99.99%, from Hebei Sanliujiu New Materials Technology Co., Ltd. Copper particles: 3-5mm, purity 99.9%, from Hebei Teng Bimetallic Materials Co., Ltd.; Silver nitrate: CAS No. 7761-88-8, from Guangdong Xiaoda Chemical Co., Ltd.; 5,5-Dimethylhydantoin: CAS No. 503-60-6, from Hubei Huiheyuan Chemical Co., Ltd.; Nicotinic acid: CAS No. 59-67-6, from Merck reagent; 2-Hydroxypyridine: CAS No. 142-08-5, derived from MacLean reagent; Graphene oxide: Product No. C03043, 0.5-3μm, from Beijing Juguang Evonik Technology Co., Ltd.; Ammonia: CAS No. 1336-21-6, from Merck Reagent; Potassium sodium tartrate: CAS No. 6381-59-5, from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd.; The surfactant was sodium dodecyl sulfate, CAS No. 151-21-3, from Merck Reagents; Titanium carbide: grade TiC-1, 1.5-2.0μm, from Hunan Huasheng Technology Co., Ltd.; Preparation of metal plate: iron particles, nickel particles, zinc particles, tin particles, silicon particles and copper particles are mixed and melted to obtain alloy liquid, the alloy liquid is poured into a mold, and cooled to obtain a metal plate; in terms of mass percentage, 2.2% iron, 2.0% nickel, 1.0% zinc, 0.2% tin, 0.6% silicon, and the rest is copper.
[0036] Embodiment 1: A process for silver plating a lead frame surface, comprising the following steps: 1. Preparation of pre-silver plating solution: Silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water were mixed and stirred uniformly, and the pH was adjusted to 9 to obtain a pre-silver plating solution; the ratio of silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water was 5g:60g:10g:10g:0.8L; 2. Preparation of composite silver plating solution: S1: Mix silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water, stir evenly, and adjust the pH to 11.5 to obtain a silver plating solution; the ratio of silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water is 10g:60g:60mL:3mL:0.8L; S2: placing titanium carbide particles in the above silver plating solution, magnetically stirring the reaction, washing and drying after the reaction, to obtain modified titanium carbide; the mass ratio of titanium carbide particles to silver plating solution is 1:5; the process conditions of magnetic stirring are: temperature 20°C, rotation speed 200r / min, time 20min; S3: Take half of the silver plating solution and mix it with modified titanium carbide and graphene oxide, stir it ultrasonically, then add the remaining silver plating solution, stir it evenly, and obtain a composite silver plating solution; the mass ratio of silver plating solution, modified titanium carbide, and graphene oxide is 7:0.05:0.08; the process conditions of ultrasonic stirring are: power 150w, time 60min, speed 400r / min; 3. Preparation of silver-plated lead frame: Step (1): mixing iron particles, nickel particles, zinc particles, tin particles, silicon particles and copper particles, melting them to obtain an alloy liquid, pouring the alloy liquid into a mold, cooling it, and obtaining a metal plate; step (2): placing the obtained metal plate in a pre-silvering liquid, performing a pre-silvering treatment, forming a pre-silvering layer, and obtaining a pre-silvered metal plate; step (3): attaching a layer of dry film to the upper surface and the lower surface of the pre-silvered metal plate, exposing, developing, and drying, removing part of the dry film on the upper surface and the lower surface of the pre-silvered metal plate, and etching the exposed local area of the pre-silvered metal plate to obtain a pre-silvered lead frame; step (4): placing the obtained pre-silvered lead frame in a composite silvering liquid, performing a silvering treatment, forming a composite silvering layer, and obtaining a silver-plated lead frame; the melting temperature in step (1) is 1300° C., and the cooling temperature is 20° C.; the process conditions for pre-silvering in step (2) are: current density 0.1A / dm 2 , temperature 20°C, time 3min; the exposure process conditions in step (3) are: ambient temperature 20°C, time 15s, light intensity 500MJ; development time is 100s; the silver plating process conditions in step (4) are: voltage 300V, current 15A, frequency 450Hz, time 0.5h.
[0037] Embodiment 2: A process for silver plating a lead frame surface, comprising the following steps: 1. Preparation of pre-silver plating solution: Silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water were mixed and stirred uniformly, and the pH was adjusted to 10 to obtain a pre-silver plating solution; the ratio of silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water was 7g:70g:20g:20g:0.9L; 2. Preparation of composite silver plating solution: S1: Mix silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water, stir evenly, and adjust the pH to 12 to obtain a silver plating solution; the ratio of silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water is 15g:80g:70mL:5mL:0.9L; S2: placing titanium carbide particles in the above silver plating solution, magnetically stirring the reaction, washing and drying after the reaction, to obtain modified titanium carbide; the mass ratio of titanium carbide particles to silver plating solution is 1:6; the process conditions of magnetic stirring are: temperature 25°C, speed 250r / min, time 25min; S3: Take half of the silver plating solution and mix it with modified titanium carbide and graphene oxide, stir it ultrasonically, then add the remaining silver plating solution, stir it evenly, and obtain a composite silver plating solution; the mass ratio of silver plating solution, modified titanium carbide, and graphene oxide is 8:0.08:0.1; the process conditions of ultrasonic stirring are: power 170w, time 70min, speed 500r / min; 3. Preparation of silver-plated lead frame: Step (1): mixing iron particles, nickel particles, zinc particles, tin particles, silicon particles and copper particles, melting them to obtain an alloy liquid, pouring the alloy liquid into a mold, cooling it, and obtaining a metal plate; step (2): placing the obtained metal plate in a pre-silvering liquid, performing a pre-silvering treatment, forming a pre-silvering layer, and obtaining a pre-silvered metal plate; step (3): attaching a layer of dry film to the upper surface and the lower surface of the pre-silvered metal plate, exposing, developing, and drying, removing part of the dry film on the upper surface and the lower surface of the pre-silvered metal plate, and etching the exposed local area of the pre-silvered metal plate to obtain a pre-silvered lead frame; step (4): placing the obtained pre-silvered lead frame in a composite silvering liquid, performing a silvering treatment, forming a composite silvering layer, and obtaining a silver-plated lead frame; the melting temperature in step (1) is 1350° C., and the cooling temperature is 25° C.; the process conditions for pre-silvering in step (2) are: current density 0.2A / dm 2 , temperature 25°C, time 4min; the exposure process conditions in step (3) are: ambient temperature 30°C, time 20s, light intensity 800MJ; development time is 140s; the silver plating process conditions in step (4) are: voltage 340V, current 20A, frequency 500Hz, time 1h.
[0038] Embodiment 3: A process for silver plating a lead frame surface, comprising the following steps: 1. Preparation of pre-silver plating solution: Silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water are mixed and stirred uniformly, and the pH value is adjusted to 11 to obtain a pre-silver plating solution; the ratio of silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water is 9g:80g:30g:30g:1L; 2. Preparation of composite silver plating solution: S1: Mix silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water, stir evenly, and adjust the pH to 12.5 to obtain a silver plating solution; the ratio of silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water is 20g:100g:80mL:6mL:1L; S2: placing titanium carbide particles in the above silver plating solution, magnetically stirring the reaction, washing and drying after the reaction, to obtain modified titanium carbide; the mass ratio of titanium carbide particles to silver plating solution is 1:7; the process conditions of magnetic stirring are: temperature 30°C, rotation speed 300r / min, time 30min; S3: Take half of the silver plating solution and mix it with modified titanium carbide and graphene oxide, stir it ultrasonically, then add the remaining silver plating solution, stir it evenly, and obtain a composite silver plating solution; the mass ratio of silver plating solution, modified titanium carbide, and graphene oxide is 9:0.1:0.12; the process conditions of ultrasonic stirring are: power 200w, time 80min, speed 600r / min; 3. Preparation of silver-plated lead frame: Step (1): mixing iron particles, nickel particles, zinc particles, tin particles, silicon particles and copper particles, melting them to obtain an alloy liquid, pouring the alloy liquid into a mold, cooling it, and obtaining a metal plate; step (2): placing the obtained metal plate in a pre-silvering liquid, performing a pre-silvering treatment, forming a pre-silvering layer, and obtaining a pre-silvered metal plate; step (3): attaching a layer of dry film to the upper surface and the lower surface of the pre-silvered metal plate, exposing, developing, and drying, removing part of the dry film on the upper surface and the lower surface of the pre-silvered metal plate, and etching the exposed local area of the pre-silvered metal plate to obtain a pre-silvered lead frame; step (4): placing the obtained pre-silvered lead frame in a composite silvering liquid, performing a silvering treatment, forming a composite silvering layer, and obtaining a silver-plated lead frame; the melting temperature in step (1) is 1400° C., and the cooling temperature is 30° C.; the process conditions for pre-silvering in step (2) are: current density 0.3A / dm 2 , temperature 30°C, time 5min; the exposure process conditions in step (3) are: ambient temperature 40°C, time 25s, light intensity 1000MJ; the development time is 180s; the silver plating process conditions in step (4) are: voltage 380V, current 25A, frequency 650Hz, time 1.5h.
[0039] Comparative Example 1: Using Example 1 as a comparison, the lead frame is not pre-silver-plated, and other conditions remain unchanged.
[0040] Comparative Example 2: Using Example 1 as a comparison, the titanium carbide in the silver plating solution was not surface modified, and the other conditions remained unchanged.
[0041] Comparative Example 3: Compared with Example 1, graphene oxide is not added to the silver plating solution, and other conditions remain unchanged.
[0042] Experiment: Take the silver-plated lead frames obtained in Examples 1 to 3 and Comparative Examples 1 to 3, test their various properties and record the test results: According to GB / T20254-2015, the conductivity, tensile strength and hardness of the manufactured silver-plated lead frame are tested; According to GB / T1771-2007, the salt spray resistance of the prepared silver-plated lead frame was tested, with the temperature controlled at 40°C, pH 6.0, sodium chloride concentration 60g / L, and time 500h; The following table shows the test results of conductivity, tensile strength, hardness, and salt spray resistance of the silver-plated lead frame;
[0043] According to the data in the above table, we can clearly draw the following conclusions: The silver-plated lead frames obtained in Examples 1-3 are compared with the silver-plated lead frames obtained in Comparative Examples 1-3. The test results show that: Compared with Example 1, Comparative Example 1 does not pre-silver-plating the lead frame, and its conductivity decreases significantly. This is because the lead frame is directly placed in the silver-plating solution, and the copper ions in the lead frame will undergo a replacement reaction with the silver-plating solution, destroying the stability of the silver-plating solution, affecting the silver-plating effect, resulting in uneven distribution of the silver-plated layer, and a decrease in conductivity. Compared with Example 1, Comparative Example 2 does not perform surface modification on titanium carbide in the silver plating solution, and its tensile strength, hardness and salt spray resistance are reduced because the dispersibility of titanium carbide in the silver plating solution is reduced, so the formed silver plating layer is uneven, resulting in a decrease in the overall performance of the silver-plated lead frame; Compared with Example 1, in Comparative Example 3, graphene oxide is not added to the silver plating solution, and its tensile strength, hardness and salt spray resistance are significantly reduced. This is because the epoxy functional groups on the surface of the graphene oxide can form a self-assembled monolayer on the surface of the lead frame substrate, thereby enhancing the bonding force between the silver-plated layer and the substrate. After the graphene oxide is removed, the bonding force decreases, and the silver-plated layer is easy to fall off, resulting in a decrease in the overall performance of the silver-plated lead frame. It can be seen that the material settings used in this application can promote the improvement of the conductivity, tensile strength, hardness and salt spray resistance of the manufactured silver-plated lead frame.
[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A lead frame, characterized in that: It comprises a metal plate and a silver-plated layer, wherein the silver-plated layer comprises a pre-silver-plated layer and a composite silver-plated layer; The composite silver-plated layer comprises the following components: metallic silver, modified titanium carbide, and graphene oxide; The modified titanium carbide is titanium carbide that has been subjected to silver coating treatment.
2. A process for silver plating the surface of a lead frame, characterized in that: The following steps are involved: Step 1: placing the metal plate in a pre-silvering solution to perform a pre-silvering treatment to form a silver-plated layer to obtain a pre-silvered metal plate; Step 2: attaching a layer of dry film on the upper surface and the lower surface of the pre-silver-plated metal plate, exposing, developing, and drying, removing part of the dry film on the upper surface and the lower surface of the pre-silver-plated metal plate, and etching the exposed local area of the pre-silver-plated metal plate to obtain a pre-silver-plated lead frame; Step 3: placing the obtained pre-silver-plated lead frame in a composite silver-plating solution, performing a silver-plating treatment, forming a silver-plated layer, and obtaining a silver-plated lead frame.
3. The process for silver plating the surface of a lead frame according to claim 2, characterized in that: The pre-silver plating solution described in step 1 is prepared by the following process: Silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water are mixed and stirred uniformly, and the pH is adjusted to 9-11 to obtain a pre-silver plating solution.
4. The process for silver plating the surface of a lead frame according to claim 2, characterized in that: The composite silver plating solution in step 3 is prepared by the following process: Half of the silver plating solution is mixed with modified titanium carbide and graphene oxide, and ultrasonically stirred, and then the remaining silver plating solution is added and stirred evenly to obtain a composite silver plating solution.
5. The process for silver plating the surface of a lead frame according to claim 4, characterized in that: The modified titanium carbide is prepared by the following process: The titanium carbide particles are placed in a composite silver plating solution, subjected to magnetic stirring for reaction, and then washed and dried to obtain modified titanium carbide.
6. The process for silver plating the surface of a lead frame according to claim 3, characterized in that: The ratio of silver nitrate, 5,5-dimethylhydantoin, nicotinic acid, 2-hydroxypyridine and deionized water is (5-9) g: (60-80) g: (10-30) g: (10-30) g: (0.8-1) L.
7. The process for silver plating the surface of a lead frame according to claim 4, characterized in that: The mass ratio of silver plating solution, modified titanium carbide and graphene oxide is (7-9): (0.05-0.1): (0.08-0.12).
8. The process for silver plating the surface of a lead frame according to claim 2, characterized in that: The process conditions for pre-silvering in step 1 are: current density 0.1-0.3A / dm 2 , temperature 20-30℃, time 3-5min.
9. The process for silver plating the surface of a lead frame according to claim 2, characterized in that: The process conditions for silver plating in step 3 are: voltage 300-380V, current 15-25A, frequency 450-650Hz, time 0.5-1.5h.
10. The process for silver plating the surface of a lead frame according to claim 4, characterized in that: The silver plating solution is made by the following process: Silver nitrate, sodium potassium tartrate, ammonia water, surfactant and distilled water are mixed, stirred evenly, and the pH is adjusted to 11.5-12.5 to obtain a silver plating solution.